Pendampingan Penyusunan Rencana Pembangunan Jangka Menengah Desa (RPJMDes) Kampung Aimo, Distrik Aimas, Kabupaten Sorong - Ibal, La; Madaul, Rahful A.; Hilmansyah, Hilmi; Marshush, Ummi Hanifah; Abubakar, Endang; Murni, Murni; Salam, Rahmi Ariani; Wulandari, Mega; Widodo, Slamet; Klau, Stevanus Viki (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The Village Medium-Term Development Plan (RPJMDes) serves as a fundamental framework for steering village development across a six-year span. Nevertheless, numerous villages encounter significant obstacles in drafting this plan, primarily due to constrained human resources and a lack of technical proficiency. This community engagement initiative seeks to support the local administration of Aimo Village in formulating an RPJMDes that prioritizes community involvement, relies on accurate data, and adheres to regulatory standards. The approach adopted encompasses capacity-building sessions, collaborative dialogues, and hands-on technical guidance. Findings reveal that a preliminary version of the RPJMDes was effectively crafted, incorporating the village leader’s vision and mission, strategic policy outlines, and a structured set of priority development initiatives. Furthermore, the process bolstered the skills of village officials and fostered greater public engagement in shaping development plans.